Robust GMR sensors for angle detection and rotation speed sensing - Giebeler, C.; Adelerhof, D.J.; Kuiper, A.E.T.; van Zon, J.B.A.; Oelgeschläger, D.; Schulz, G. (Sensors and actuators. A. Physical., 2001)
Magnetic sensors for automotive applications based on the giant magnetoresistance (GMR) effect have been developed. These sensors combine many of the advantageous properties of the GMR effect for sensor applications. The sensor characteristics have been optimised with respect to two different applications, namely angular position sensing and rotational speed sensing. Robust GMR sensors with a full Wheatstone-bridge configuration have been fabricated. The thermal and magnetic stability of our GMR sensors are excellent. The sensors show reliable performance at temperatures exceeding 170°C and at large magnetic fields (>200 kA/m). Lifetime tests at elevated temperatures also show very promising results.